2022
DOI: 10.1002/pcn5.5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms and related risk factors among healthcare workers and medical students during the early phase of the COVID‐19 pandemic in Japan

Abstract: Aim The aim of this study was to investigate the mental health status of healthcare workers and medical students during the early phase of the COVID‐19 pandemic. Methods An online questionnaire was administered to 637 students and 3189 healthcare workers from May to July, 2020. The patient healthcare questionnaire‐9 (PHQ‐9) and state anxiety (A‐State) of the state–trait anxiety inventory‐form (STAI) were used to assess depression and anxiety symptoms, respectively. Individuals were categorized into severe (15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that anxiety correlates independently with depression and suicide-related ideation [ 47 49 ]. However, a previous study on HCWs and medical students in Japan showed that the severity of depression symptoms was not correlated with anxiety symptoms [ 50 ]. Although it may be essential to differentiate anxiety disorder from anxiety symptoms or ‘anxiety’ from COVID-19 infection here in our analysis, our analysis showed that recognizing or expressing ‘anxiety’ from infection could be a protective factor for suicide-related ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that anxiety correlates independently with depression and suicide-related ideation [ 47 49 ]. However, a previous study on HCWs and medical students in Japan showed that the severity of depression symptoms was not correlated with anxiety symptoms [ 50 ]. Although it may be essential to differentiate anxiety disorder from anxiety symptoms or ‘anxiety’ from COVID-19 infection here in our analysis, our analysis showed that recognizing or expressing ‘anxiety’ from infection could be a protective factor for suicide-related ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Asian populations seem to have a more elevated STAI-state under comparable circumstances. One study on 637 Japanese medical students reported a mean STAI-state score of 42 (39–46 interquartile range) ( Tanifuji et al, 2022 ). In fact, previous studies conducted in Japan and India showing efficacy of probiotics have reported STAI-state scores above 40 at baseline, and the participants included also reported a smaller variation in this parameter ( Nishida et al, 2017 ; Venkataraman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…State anxiety refers to a specific threat of a shorter duration that may disappear as the threat weakens [ 13 ]; in this case, the COVID-19 outbreak [ 14 ]. Spielberger also developed the State-Trait Anxiety Inventory (STAI) to assess anxiety [ 12 ], which has been validated among students, adults, medical patients, health care workers, and recently in the context of the COVID-19 pandemic [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%